Potensi Pengusulan Jenis Baru Peronosclerospora sorghi Asal Nusa Tenggara Timur - Ummu Salamah Rustiani; Meity Suradji Sinaga; Sri Hendrastuti Hidayat; Suryo Wiyono; Darni Rambu D. Siala (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2021)
Potential Proposal for A New Type of Peronosclerospora Sorghi from East Nusa Tenggara Downy mildew of corn caused by Peronosclerospra can cause real economic damage. In Indonesia, it is known that there are three species of Peronosclerospora, namely P. maydis, P. phillippinenis, and P. sorghi. Peronosclerospora maydis is the dominant species found in Indonesia. The three species can be identified from their morphological and molecular characters. However, the results of monitoring by the Kupang Agricultural Quarantine Station during 2016-2019 showed that the morphological characteristics of P. sorghi from NTT are different from the morphology from Java and Sulawesi in terms of the number of sterigmata formed from conidiophores. The number of P. sorghi sterigmata from NTT is less than in other locations. This will lead to a smaller number of conidia produced by P. sorghi from NTT. Based on the molecular analysis, the character of P. sorghi isolate from NTT is in a separated family tree from Java and Sulawesi isolates but is included in one group with P. sorghi isolates from USA. The results of morphological and molecular studies showed further study on host ranges, genetic diversity of the fungal isolates as well as shorgum should be considered in the future. Sorghum as the primary host of P. sorghi has been gathered for the genetic data of sorghum originating from NTT and then comparing to the data from Texas, USA. That information will be contributing to determine the identity of P. sorghi from NTT.